2018
DOI: 10.7126/cumudj.410459
|View full text |Cite
|
Sign up to set email alerts
|

Farklı Profilaktik Parlatma İşlemlerinin Mikrohibrit ve Nanohibrit Kompozit Rezinlerin Yüzey Pürüzlülüğü Üzerine Etkisi

Abstract: Bu çalışmanın amacı, farklı profesyonel dental profilaksi işlemlerinin bir mikrohibrit (Charisma, Heraeus-Kulzer) ve bir nanohibrit (Ice, SDI Dental) kompozit rezinin yüzey pürüzlülüğü üzerine etkisini değerlendirmektir. Gereç ve Yöntem: Her restoratif materyalden 45 adet disk şekilli örnek (2 mm kalınlık ve 8 mm çapında, toplam 90 örnek) plastik kalıplar kullanılarak hazırlandı. Örnekler orta, ince ve ultra ince grenli Sof-Lex (3M-ESPE) disklerle parlatıldı ve her kompozitten 45 örnek rastgele beş gruba ayrıl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…26 It has been reported that the CIEDE2000 formula re ects the color differences that the human eye can detect better than the CIE Lab formula. 27 Yamanel et al, in their study, suggested that due to the very small size of the inorganic ller particles in the structure of the restorative materials containing nano llers, smoother surfaces can be obtained after nishing and polishing compared to microhybrid composites. 27 In our study, the nanohybrid restorative material G-aenial was found to show statistically signi cantly less surface roughness than the microhybrid restorative Fill-up.…”
Section: Discussionmentioning
confidence: 99%
“…26 It has been reported that the CIEDE2000 formula re ects the color differences that the human eye can detect better than the CIE Lab formula. 27 Yamanel et al, in their study, suggested that due to the very small size of the inorganic ller particles in the structure of the restorative materials containing nano llers, smoother surfaces can be obtained after nishing and polishing compared to microhybrid composites. 27 In our study, the nanohybrid restorative material G-aenial was found to show statistically signi cantly less surface roughness than the microhybrid restorative Fill-up.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the measurements obtained with a spectrophotometer are converted into three different color parameters based on the Commission Internationale de l'Elcairage (CIE)L*a*b* and CIEDE 2000 color systems and calculated as ∆E* values in line with these values [24]. It has been reported that the CIEDE 2000 formula reflects the color differences that the human eye can detect better than the CIE Lab formula [25].…”
Section: Discussionmentioning
confidence: 99%
“…Yamanel et al [25], in their study, suggested that due to the very small size of the inorganic filler particles in the structure of the restorative materials containing nanofillers, smoother surfaces could be obtained after the finishing and polishing of these materials than after that of microhybrid composites.…”
Section: Discussionmentioning
confidence: 99%